(untitled) (Journal of Geography and Environmental Management, 2025)
Ghizil-Agaj Bay is a wetland of international importance located in the southeastern part of Azerbaijan and included in the Ramsar Convention list. Over the past 30 years, anthropogenic impacts on this ecosystem, along with natural factors, have intensified, leading to significant changes in the morphological and hydrological characteristics of the shoreline. The aim of this study is to assess the dynamics of the coastline in the Gizil-Agach Bay and to evaluate its impact on biodiversity. This study analysed shoreline dynamics from 2000 to 2024 using Landsat and Sentinel-2 imagery, Geographic Information Systems, and the Digital Shoreline Analysis System. Results revealed significant spatiotemporal shoreline changes, with maximum progradation of +570 m/year and maximum erosion of –4 m/year. Between 2000 and 2024, approximately 240 km² of land was gained, while 0.56 km² of water area was lost. These changes influenced wetland ecosystem extent and quality, causing shifts in avifauna and biodiversity: migratory water bird nesting and feeding habitats declined, total water bird numbers decreased by approximately 28%, while terrestrial bird species nesting on newly emerged land increased by approximately 12%. These findings can serve as a basis for wetland management policies under climate change conditions.